P2RX1-Involved Glycolytic Metabolism Supports Neutrophil Activation in Acute Pancreatitis - Wang, Xu; Liu, Dadong; Qin, Weiting; Liu, Yishu; Yuan, Xiao; Zhang, Xiaoxin; Dai, Chunhua; Zhang, Danyi (Frontiers in Immunology, 2021)
Acute pancreatitis (AP) is characterized by disordered inflammation of pancreas, and the underlying mechanisms remains unclear. Purinergic signaling plays crucial roles in initiating and amplifying inflammatory signals. Recent evidence reveals that targeting dysregulated purinergic signaling is promising for treating inflammation-associated diseases. To explore the potential involvement of purinergic signaling in AP, we investigated the expression profiles of purinergic signaling molecules in human and mouse pancreas tissues. Results showed that purinergic receptor P2RX1 was among the most highly expressed genes in both human and mouse pancreas tissues. Genetic ablation or specific antagonism of P2RX1 markedly alleviated inflammatory responses in caerulein-induced AP mice. Bone marrow chimeras and adoptive transfer studies revealed that neutrophil-derived P2RX1 contributed to the inflammatory responses in AP. Further studies demonstrated that P2RX1 promoted neutrophil activation by facilitating glycolytic metabolism. Therefore, our study indicates that purinergic receptor P2RX1 may be a potential therapeutic target to treat disordered inflammation in AP.